Multicompartment Ecosystem Mass Balances as a Tool for Understanding and Managing the Biogeochemical Cycles of Human Ecosystems - Lawrence A. Baker; Diane Hope; Ying Xu; Jennifer Edmonds (The Scientific World Journal)
Nitrogen remains a ubiquitous pollutant in surface and groundwater throughout the United States, despite 30 years of pollution control efforts. A detailed multicompartment N balance for the Central Arizona-Phoenix ecosystem is used to illustrate how an ecosystem-level approach can be used to develop improved N management strategies. The N balance is used to demonstrate how nitrate in pumped groundwater used for crop irrigation could be used to reduce inputs of commercial fertilizer and decrease N leaching to aquifers. Effectively managing N pollution also will require an understanding of the complex factors that control the N balance, including targeted regulations, individual human behavior, land-use conversion, and other ecosystem management practices that affect the N balance. These sometimes countervailing factors are illustrated with several scenarios of wastewater treatment technology and population growth in the Phoenix area. Management of N eventually must be coupled to management of other elements, notably carbon, phosphorus, and salts. We postulate that an ecosystem framework for pollution management will result in strategies that are more effective, fairer, and less expensive than current approaches.